Neuropsychiatric adverse events in people with HIV initiating a new integrase strand transfer inhibitor-based regimen in Italy: findings from the NEURO-INSTI study - Nicola Squillace; Elena Delfina Ricci; Giancarlo Orofino; Gabriele Forcina; Laura Albini; Barbara Menzaghi; Giuseppe Vittorio De Socio; Stefania Piconi; Paolo Maggi; Giordano Madeddu; Giovanni Francesco Pellicanò; Eleonora Sarchi; et al. (BMC Infectious Diseases)
Abstract Background Although clinical trials reported a low and comparable rate of central nervous system (CNS)/neuropsychiatric (NP) disturbances among people with HIV (PWH) receiving integrase strand transfer inhibitors (INSTI) or other antiretroviral therapy (ART), higher rates of these disturbances have been reported in clinical practice. Our aim was to compare the occurrence of CNS-NP disorders in the different INSTI drugs. Methods Using data from the SCOLTA project, a multicenter observational study following PWH who start antiretrovirals to identify adverse events (AEs) in real-life, we performed a retrospective analysis (NEURO-INSTI) to assess incidence rates (IRs) and 95% confidence intervals (95% CI) of CNS/NP AEs and related interruptions. Observation was truncated at the first occurrence of any CNS/NP AEs, even if not causing treatment discontinuation. IRs were calculated as number of first occurrences/100 person-years follow-up (PYFU). To identify risk factors for CNS/NP AEs occurrence, a Cox regression analysis for competing risks was used (hazard ratio, HR, and 95% CI), including variables associated with the outcome at a p level < 0.20 in the univariate analysis. Results We analyzed a sample of 2,922 PWH (mean age 47.2 years, 74.7% males) enrolled in raltegravir (RAL), dolutegravir (DTG), elvitegravir (EVG), and bictegravir (BIC) INSTI-cohorts since 2007. Over a median observation time of 28 months (interquartile range 14–45), 126 CNS/NP AEs and 72 related discontinuations occurred; IRs were 1.59/100 PYFU (95% CI, 1.34–1.90) and 0.91/100 PYFU (95% CI 0.72–1.15), respectively. In multivariate models, intravenous drug use history (IVDUh), current abacavir use, RAL use, and psychiatric illnesses were associated with a higher risk of CNS/NP AEs. IVDUh and current abacavir use were also associated with treatment discontinuation. Using an INSTI as a first-line therapy and starting with CD4 ≥ 350 cell/µL also increased the likelihood of discontinuation. Compared to DTG, BIC and EVG showed lower risks of CNS/NP AEs (adjusted HR 0.27, 95% CI 0.10–0.74, and 0.51, 95% CI 0.22–1.20, respectively), while RAL showed a higher risk (aHR 2.52, 95% CI 1.57–4.05). Conclusions Among PWH on INSTI treatment, IVDUh, concurrent psychiatric illness, abacavir and RAL use increased the risk of CNS/NP AEs occurrence. PWH on BIC were less likely to experience CNS/NP AEs and related treatment discontinuations.